Experimental and DFT study of azo-bis-cyanuric chloride polar Diels-Alder reaction with a number of dienes. Ways of further modification of the obtained products - Karkhut, Andriy; Polovkovych, Svyatoslav; Novikov, Volodymyr (Lviv Politechnic Publishing House, 2018)
Була проведена та досліджена на B3LYP/6-31G(d,p) рівні реакція Дільса-Альдера азо-біс- ціанурхлориду як електрофільного дієнофілу з рядом дієнів з різною нуклеофільністю, а саме 2,3-диметилбутадієну, 2-ме- тилбутадієну і 1-ацетоксибутадієну. Визначено, що реакція проходить за м’яких умов та з високими виходами. Обчислені глобальні та локальні індекси реакційності, а також геометрії перехідних станів та енергії активації. Вивчені напрямки подальшої модифікації одержаних продуктів заміщенням атомів хлору. Встановлено, що сполуки є стійкими в лужних умовах, але швидко руйнуються у присутності кислот.

The reaction of azo-bis-cyanuric chloride as strong electrophilic aza-dienophile in Diels-Alder cycloaddition with a number of dienes of different nucleophilicity, namely 2,3-dimethylbutadiene, 2-methylbutadiene and 1-acethoxybutadiene, was carried out and computationally analyzed on B3LYP/6-31G(d,p) level. Local and global reactivity indices, based on FMO theory, as well as TS geometries and activation energies were calculated. Reaction proceeds rapidly with high yields and in mild conditions. Ways of products further modification by chlorine atoms substitution were also studied. Compounds were found to be stable in alkaline conditions but rapidly decompose in the presence of acids.
Експериментальні та DFT-дослідження полярної реакції Дільса-Альдера азо-біс- ціанурхлориду з рядом дієнів. Шляхи подальшоїмодифікації одержаних продуктів
Keywords: реакція Дільса-Альдера; DFT розра- хунки; 1; 3; 5-триазин; конформаційний аналіз; Diels-Alder reaction; DFT calculations; 1; 3; 5-triazine; conformational analysis